2014
DOI: 10.1016/j.culher.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in lighting for enhancing the appreciation and preservation of archaeological heritage

Abstract: a b s t r a c tThe cultural content of ancient sites highlights the importance of light, which is an essential tool for the correct appreciation of the historical value and memory of cultural heritage. This should be a new way to highlight significance of fragments in compliance of the surrounding, which has not the same characteristics, to signal a visual path, creating itineraries that involve the context. Light plays a very important role in creating emotion, suggestion, evocation and supporting the visitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
0
12
0
2
Order By: Relevance
“…Results have shown that this method will allow for adaptive lighting, based on the optimal control and use of natural light, historical-philological re-reading of the space, cultural heritage preventive protection and conservation, with the aim of building adaptive reuse, and it can be extended to similar cultural heritage cases, but also non-listed buildings and current designs. This research demonstrates how a correct natural lighting design can be a tool for sustainable refurbishment, guaranteeing cultural heritage conservation and preventive protection, and recovery of the historical, architectural and philological value of old and/or listed buildings, which have been converted to uses, often diametrically opposed to the original ones.Sustainability 2019, 11, 4842 2 of 17 libraries, especially when housed in historical buildings, highlighting its positive effects (i.e., economic, management, social, cultural, political, energy and environmental [10,13-16]), for the connection between recovery and conservative restoration of valuable historical buildings, with adaptive reuse as an essential component of sustainable new design and/or refurbishment [11,12,[17][18][19][20][21][22].This issue is complex just because historical buildings have often been converted to different uses from the original ones and natural light quantity and distribution in the environment can become the cause of deterioration and damage for sensitive materials and objects [14,[18][19][20][21].With regard to the issue concerning damage caused by exposure to light (e.g., radiant heating, photochemical action, structural degradation), for the preventive conservation and protection of high light-sensitive materials, such as textiles, carpets, tapestries, costumes, prints, books and paper material, the maximum illuminance value suggested is 50 lx. For low light-sensitive materials, such as stone materials, the suggested value is 300 lx and for average light-sensitive materials such as organic materials and wood, the suggested value is 150 lx [14,[18][19][20][21].Any retrofit and refurbishment solution for a new lighting system that does not recall the luminous climate belonging to the history of the building, does not allow the historical-philological reading of the space, does not transmit contents and information, can alter the visual perception up to making the space (historical building) even unrecognizable [3,20,21].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Results have shown that this method will allow for adaptive lighting, based on the optimal control and use of natural light, historical-philological re-reading of the space, cultural heritage preventive protection and conservation, with the aim of building adaptive reuse, and it can be extended to similar cultural heritage cases, but also non-listed buildings and current designs. This research demonstrates how a correct natural lighting design can be a tool for sustainable refurbishment, guaranteeing cultural heritage conservation and preventive protection, and recovery of the historical, architectural and philological value of old and/or listed buildings, which have been converted to uses, often diametrically opposed to the original ones.Sustainability 2019, 11, 4842 2 of 17 libraries, especially when housed in historical buildings, highlighting its positive effects (i.e., economic, management, social, cultural, political, energy and environmental [10,13-16]), for the connection between recovery and conservative restoration of valuable historical buildings, with adaptive reuse as an essential component of sustainable new design and/or refurbishment [11,12,[17][18][19][20][21][22].This issue is complex just because historical buildings have often been converted to different uses from the original ones and natural light quantity and distribution in the environment can become the cause of deterioration and damage for sensitive materials and objects [14,[18][19][20][21].With regard to the issue concerning damage caused by exposure to light (e.g., radiant heating, photochemical action, structural degradation), for the preventive conservation and protection of high light-sensitive materials, such as textiles, carpets, tapestries, costumes, prints, books and paper material, the maximum illuminance value suggested is 50 lx. For low light-sensitive materials, such as stone materials, the suggested value is 300 lx and for average light-sensitive materials such as organic materials and wood, the suggested value is 150 lx [14,[18][19][20][21].Any retrofit and refurbishment solution for a new lighting system that does not recall the luminous climate belonging to the history of the building, does not allow the historical-philological reading of the space, does not transmit contents and information, can alter the visual perception up to making the space (historical building) even unrecognizable [3,20,21].…”
mentioning
confidence: 99%
“…Sustainability 2019, 11, 4842 2 of 17 libraries, especially when housed in historical buildings, highlighting its positive effects (i.e., economic, management, social, cultural, political, energy and environmental [10,13-16]), for the connection between recovery and conservative restoration of valuable historical buildings, with adaptive reuse as an essential component of sustainable new design and/or refurbishment [11,12,[17][18][19][20][21][22].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…From this point of view, Tural and Yener [18] suggested the need for monument lighting, taking it as an essential architectural and outdoor lighting issue, and they evaluated different lighting conditions of the Bilkent University Atatürk Monument. Di Salvo [19] focused on the importance of respecting the authenticity of sites trying to show both their historical and architectural value, and four different sites were taken into consideration in this study: the archaeological crypt of Notre Dame in Paris, La Ciutadella de Roses in Catalonia, the London's Roman amphitheater and the archaeological Park of Selinunte. On the other hand, Cevik et al [20] stressed, through the analysis of Kunduracilar Street in Trabzon (Tuekry), how a lighting installation, able to emphasize the characteristics of historic buildings, can play an important role in renovation-revitalization works in historical city centres.…”
Section: Introductionmentioning
confidence: 99%